Pengaruh Variasi Beban Produk Terhadap Kerja Kompresor Pada Sistem Ice Maker Berbasis Brine Cooling - Marvelyano Petra Sampara; Cendy Sophia Edwina Tupamahu; Sefnath Josep Etwan Sarwuna (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Refrigeration systems play a crucial role in cooling and freezing processes within low-temperature-based industries. In brine cooling-based ice maker systems, performance is highly dependent on the compressor as the primary component in the vapor compression cycle. Variations in product load lead to changes in heat load, which directly affect compressor work and energy consumption. This study aims to analyze the effect of product load variations on compressor work and electrical power consumption. An experimental method was employed with load variations of 25, 30, and 35 water packages (0.8 kg per package). The observed parameters included pressure, temperature, compressor work, and power consumption. Data were collected through direct measurements using K-type thermocouples, manifold gauges, and watt meters, and subsequently analyzed based on vapor compression cycle equations. The results indicate that increasing the product load raises compressor work from 72.54 kJ/kg to 73.47 kJ/kg and power consumption from 5797.8 Watts to 6842.86 Watts. Additionally, higher loads result in increased discharge pressure, compressor outlet temperature, and longer freezing time. It can be concluded that product load significantly affects system performance and energy consumption.